Padrão de castas e ocorrência de um fungo actoparasita em rhinothermitida (insecta: Iisoptera) - Barbosa, José Renato Chagas (2015)
Rhinotermitidae exhibits a diverse pattern of castes. Such variation may occur due to the polyphyletic aspect of this group. Heterotermes longiceps and Rhinotermes marginalis belong to different subfamilies within Rhinotermitidae. Considering the presented so far in literature, could be the castes patterns of these species similar to observed in their subfamilies? To adress this question, caste differentiation patterns of H. longiceps and R. marginalis were investigated by morphometric data. Specimens from six colonies of H. longiceps and four R. marginalis were collected, fixed in FAA for 24 h and then transferred to 80% alcohol. Termites were separated by caste and instars and measured. Eleven morphometric variables were inspected by means of a principal components analysis (PCA). Sex differentiation of the apterous caste was carried using carmine dye in dissected specimens. PCA inspection of H. longiceps grouped two larvae instars, two worker instars, pre-soldier, minor soldier, major soldier, four instars of nymphs and alate. Sexual dimorphism in H. longiceps was achieved only by soldiers. PCA inspection for R. marginalis data grouped five larvae instar, two pre-soldier instars, two soldier instars, two worker instars, ergatoid and three instar of nymphs. All apterous were females. Only true workers were observed in each species analysed. H. longiceps caste pattern is similar to already described for Heterotermitinae and Coptotermitinae. R. marginalis showed a pattern already known to Rhinotermitinae, which is a monophyletic group. Developed gonads were not observed in specimens described as morphological ergatoids.